Principles of horticulture - Adams, C. R.; Bamford, K.; Early, M. P. (London Routledge, 2012)
"This colourful guide will introduce you to the fundamentals of horticulture. It is written in a clear and accessible style and covers the principles that underpin growing plants for the garden and allotment, with reference to how these are tackled by professionals. With highlighted definitions, key points, and illustrated in full colour, this book will be a useful companion as you progress in the study and practice of horticulture. The book covers topics such as, classifying and naming plants, the plant life cycle, ecology and garden wildlife, plant nutrition, plant pests, and plant diseases and disorders. The new edition has been updated to reflect changes in legislation and the modernisation of horticultural practices. It is also fully reflective of the changes in the new syllabuses for horticulture at level 2. Principles of Horticulture is a valuable resource whether you are taking a Level 2 RHS, City and Guilds or BTEC course, are a keen amateur or seasoned gardener. The book is accompanied by ancillary materials including essential and extended information on horticultural principles, and downloadable instructor resources"--
Keywords: Horticulture -- Textbooks